Perubahan Perilaku Konsumtif Masyarakat dari Pasar Tradisional ke Pasar Modern - Pramudiana, Ika Devy (Prodi Sosiologi Agama, 2017)
Along with the growth of advanced economies, especially in larger cities, there have been changes in various sectors including industry and production and the modern market. On the other hand, there is a shift from traditional lifestyles to modern ones, creating changes in consumer spending patterns. The purpose of this study was to determine the impact of the construction of modern markets on the economy and people’s lifestyles and the second factor is that most affect consumers’ decision to shop in modern markets more than in the traditional market. In this study, using the research method Qualitative Results obtained from this study the change in the consumer behavior of society from traditional markets to modern markets due to several factors, one of which is the modern market provides convenient facilities and women in an urban general career that almost did not have time to shop traditional markets.